Correlation of Voice Handicap Index 10 with Reflux Symptom Index and Reflux Finding Score in Patients with Dysphonia - Ari Utama; Lisa Apri Yanti; Erial Bahar (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background. Voice disturbance occurs when the quality, pitch, loudness, or flexibility of other people's voices differ according to age, gender, and similar cultural groups. The Voice Handicap Index (VHI) is one of the most widely used tools worldwide to measure the physical, functional, and emotional aspects of voice disorders. This study aims to determine the correlation of voice handicap index-10 with reflux symptom index and reflux finding scores in patients with dysphonia complaints at Dr. Mohammad Hoesin General Hospital Palembang. Methods. This study is a cross-sectional study using a correlation test design that aims to determine the correlation between VHI-10 and RSI and RFS in patients with dysphonia complaints. Results. The sample of this study includes the demographic factors of the research subjects, namely age, gender, and occupation. This study shows that patients with RFS ≥ 7 affect the VHI-10 score ≥ 11 with a proportion of 72%. Conclusion. There is a moderate positive correlation between the RFS score and the VHI-10 score, where the higher the RFS value, the higher the VHI-10 score in patients with dysphonic complaints.